Effects of Multiple Stressors, Pristine or Sulfidized Silver Nanomaterials, and a Pathogen on a Model Soil Nematode Caenorhabditis elegans - Jarad P. Cochran; Phocheng Ngy; Jason M. Unrine; Christopher J. Matocha; Olga V. Tsyusko (Nanomaterials, 2024)
Previous research using the model soil nematode Caenorhabditis elegans has revealed that silver nanoparticles (AgNP) and their transformed counterpart, sulfidized AgNP (sAgNP), reduce their reproduction and survival. To expand our understanding of the environmental consequences of released NP, we examined the synergistic/antagonistic effects of AgNP and sAgNP along with AgNO3 (ionic control) on C. elegans infected with the pathogen Klebsiella pneumoniae. Individual exposures to each stressor significantly decreased nematode reproduction compared to controls. Combined exposures to equitoxic EC30 concentrations of two stressors, Ag in nanoparticulate (AgNP or sAgNP) or ionic form and the pathogen K. pneumoniae, showed a decline in the reproduction that was not significantly different compared to individual exposures of each of the stressors. The lack of enhanced toxicity after simultaneous combined exposure is partially due to Ag decreasing K. pneumoniae pathogenicity by inhibiting biofilm production outside the nematode and significantly reducing viable pathogens inside the host. Taken together, our results indicate that by hindering the ability of K. pneumoniae to colonize the nematode’s intestine, Ag reduces K. pneumoniae pathogenicity regardless of Ag form. These results differ from our previous research where simultaneous exposure to zinc oxide (ZnO) NP and K. pneumoniae led to a reproduction level that was not significantly different from the controls.